2012
DOI: 10.1080/08856257.2012.719106
|View full text |Cite
|
Sign up to set email alerts
|

Do you see what I see? School perspectives of deaf children, hearing children and their parents☆

Abstract: Perspectives on academic and social aspects of children's school experiences were obtained from deaf and hearing children and their (deaf or hearing) parents. Possible differences between (1) the views of children and their parents and (2) those of hearing children and their parents compared to deaf children and their parents were of particular interest. Overall, parents gave their children higher school friendship ratings than the children gave themselves, and hearing children and their parents were more posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
(56 reference statements)
1
18
0
1
Order By: Relevance
“…The lack of interaction in our study between gender, hearing and social performance coincide with those of another study that also found that gender did not interact with social status [100].…”
Section: Discussionsupporting
confidence: 89%
“…The lack of interaction in our study between gender, hearing and social performance coincide with those of another study that also found that gender did not interact with social status [100].…”
Section: Discussionsupporting
confidence: 89%
“…A recent study examining the concordance of children's and parents' reports of social functioning found that all parents tended to overestimate children's social success to some degree, but both deaf children and their hearing parents agreed the children were less successful than their hearing peers (Marschark et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, parents' reports may provide critical information about the children's functioning in everyday situations, and may be particularly valuable because of specific challenges involved in interviewing adolescents (Punch & Hyde 2011b). A recent study examining the concordance of children's and parents' reports of social functioning found that all parents tended to overestimate children's social success to some degree, but both deaf children and their hearing parents agreed the children were less successful than their hearing peers (Marschark et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, parent reports of hearing loss and communication abilities may not fully reflect their DHH children’s experiences (Marschark et al, 2012). Although parent reports are important and valuable, they cannot be equated with the results of assessments conducted by individuals trained to evaluate or diagnose disabilities, health conditions, or communication skills.…”
Section: Discussionmentioning
confidence: 99%